Factor Structure and Psychometric Properties of the Anxiety Sensitivity Index-3 in an Italian Community Sample - Ghisi, Marta; Bottesi, Gioia; Altoè, Gianmarco; Razzetti, Enrico; Melli, Gabriele; Sica, Claudio (Frontiers in Psychology, 2016)
Anxiety Sensitivity (AS) is defined as the fear of anxiety and of arousal-related bodily sensations, arising from erroneous beliefs that these sensations will have adverse consequences. AS plays a key role both in the onset and in the maintenance of several disorders, particularly anxiety disorders. To date, only two studies on American samples have examined the bifactor structure of the Anxiety Sensitivity Index-3 (ASI-3); therefore, findings on different cultures are needed. The main purpose of the present study was to assess the factor structure and psychometric properties of the ASI-3 in an Italian community sample. Participants were recruited from the general population (N=1507). The results of a series of confirmatory factor analyses indicated that the bifactor structure fitted the data better than the most commonly accepted structure for the measure and that it was invariant across gender. Moreover, the current study provided evidence regarding the ASI-3’s reliability and its convergent and divergent validity. Lastly, results pertaining incremental validity of the ASI-3 Physical and Cognitive Concerns subscales above and beyond the total showed that the former was not associated with a measure of physiological anxiety, whereas the latter was weakly associated with a measure of worry. Findings suggest that the ASI-3 is comprised of a dominant general factor and three specific independent factors; given the dominance of the general factor, the use of the ASI-3 total score as a measure of the general fear of anxiety is recommended in both clinical and research settings.